Mapping foundations of logical analysis to principles of microeconomics courses. (3rd March 2022) - Friesner, Daniel; Hackney, Donald D.; Schibik, Timothy J.
The undergraduate economic education literature espouses the use of critical thinking. Yet students continue to display gaps in critical thinking, and few meaningful changes have been made to teaching undergraduate economics to address this gap. This manuscript illustrates how to create a curriculum map linking foundational logical reasoning skills to an undergraduate, principles of micro-economics course. The map may be useful in identifying gaps in prerequisite logical reasoning skills and in giving a general direction to address these gaps. We find that principles of microeconomics courses require foundational logical reasoning skills comprising half of a semester-long course on logical reasoning.